Mesenchymal stem cells promote cell invasion and migration and autophagy‐induced epithelial‐mesenchymal transition in A549 lung adenocarcinoma cells. (25th January 2018) - Luo, Dan; Hu, Shiyuan; Tang, Chunlan; Liu, Guoxiang
Abstract : Mesenchymal stem cells (MSCs) are recruited into the tumour microenvironment and promote tumour growth and metastasis. Tumour microenvironment‐induced autophagy is considered to suppress primary tumour formation by impairing migration and invasion. Whether these recruited MSCs regulate tumour autophagy and whether autophagy affects tumour growth are controversial. Our data showed that MSCs promote autophagy activation, reactive oxygen species production, and epithelial‐mesenchymal transition (EMT) as well as increased migration and invasion in A549 cells. Decreased expression of E‐cadherin and increased expression of vimentin and Snail were observed in A549 cells cocultured with MSCs. Conversely, MSC coculture‐mediated autophagy positively promoted tumour EMT. Autophagy inhibition suppressed MSC coculture‐mediated EMT and reduced A549 cell migration and invasion slightly. Furthermore, the migratory and invasive abilities of A549 cells were additional increased when autophagy was further enhanced by rapamycin treatment. Taken together, this work suggests that microenvironments containing MSCs can promote autophagy activation for enhancing EMT; MSCs also increase the migratory and invasive abilities of A549 lung adenocarcinoma cells. Mesenchymal stem cell‐containing microenvironments and MSC‐induced autophagy signalling may be potential targets for blocking lung cancer cell migration and invasion.